Peripheral blood monocyte-to-lymphocyte ratio at study enrollment predicts efficacy of the RTS,S malaria vaccine: analysis of pooled phase II clinical trial data. - Warimwe, G; Fletcher, H; Olotu, A; Agnandji, S; Hill, A; Marsh, K; Bejon, P (BioMed Central, 2013)
BACKGROUND: RTS,S is the most advanced candidate malaria vaccine but it is only partially protective and the causes of inter-individual variation in efficacy are poorly understood. Here, we investigated whether peripheral blood monocyte-to-lymphocyte ratios (ML ratio), previously shown to correlate with clinical malaria risk, could account for differences in RTS,S efficacy among phase II trial participants in Africa. METHODS: Of 11 geographical sites where RTS,S has been evaluated, pre-vaccination ML ratios were only available for trial participants in Kilifi, Kenya (N = 421) and Lambarene, Gabon (N = 189). Using time to first clinical malaria episode as the primary endpoint we evaluated the effect of accounting for ML ratio on RTS,S vaccine efficacy against clinical malaria by Cox regression modeling. RESULTS: The unadjusted efficacy of RTS,S in this combined dataset was 47% (95% confidence interval (CI) 26% to 62%, P <0.001). However, RTS,S efficacy decreased with increasing ML ratio, ranging from 67% (95% CI 64% to 70%) at an ML ratio of 0.1 to 5% (95% CI -3% to 13%) at an ML ratio of 0.6. The statistical interaction between RTS,S vaccination and ML ratio was still evident after adjustment for covariates associated with clinical malaria risk in this dataset. CONCLUSION: The results suggest that stratification of study participants by ML ratio, easily measured from full differential blood counts before vaccination, might help identify children who are highly protected and those that are refractory to protection with the RTS,S vaccine. Identifying causes of low vaccine efficacy among individuals with high ML ratio could inform strategies to improve overall RTS,S vaccine efficacy. TRIAL REGISTRATION: ClinicalTrials.Gov numbers NCT00380393 and NCT00436007.